Influence of "Composite Defoliant" on Cotton Crop Yield and the Environment - Latibovna, Ikramova Makhbuba; Nimatovich, Rakhmatov Baxtiyor; Bobomurotovich, Allaqulov Davlat; Isaevich, Maxsudov Saidumar; Chorievich, Gaffarov Inoyat (Discoveries in Agriculture and Food Sciences, 2024)
The data on the use of "composite defoliant" influence on the rate of opening of the boll, leaf fall, the share of the first harvest of raw cotton are presented. The aim of the study is to reduce the doses of the defoliant Mg (ClO3) 2 Liquid by 50%, by adding Fitovak + Urea + humin, turning it into a mild defoliant, to increase the rate of opening of bolls, the share of the first harvest, the quality of cotton, protecting the soil and the atmosphere of the environment from various harmful salts. The objects of the study were the varieties "Bukhara-8", "Bukhara-10" in the conditions of moderately saline soils of the Bukhara region. Fitovak + Mg (ClO3) 2 Liquid + urea + humin was comprehensively defoliated, which has a strong effect at different times of opening of bolls by 20-30; 30-40, 40-50%. The conditions, methods of research in saline soils of the Bukhara region, the timing of the application of the "composite defoliant" depending on external factors in field and laboratory conditions were studied. The studied data proved that among the studied 2 varieties, with different terms of opening of bolls, the best indicators were 10-11-12-variants. In terms of the rate of ripening of bolls, the differences compared to the control for two varieties, respectively, were: by + 29.7-25.5-25.3%; +30.9-29.2-22.8%. The increase in the 1st cotton harvest was respectively: +10.0 +12.3 +10.7 c/ha (Bukhara-8) +6.3 +13.4 +11.7 c/ha (Bukhara-10) and was higher than the control.